Yoga Bunny - Russo, Brian (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
When Bunny wakes up, he finds it is the perfect morning to do yoga and wishes his friends would join him.
Keywords: Animals -- Fiction; Hatha yoga -- Fiction; Animals -- Fiction; Hatha yoga -- Fiction